Hubungan Kadar Gula Darah Dengan Gangguan Neuropati Perifer Pada Penderita Diabetes Mellitus Tipe 2 - Yulia Devi Putri; T. Eltrikanawati; Ariyani Ariyani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to identify the relationship between blood sugar levels and peripheral neuropathy in patients with type 2 diabetes mellitusMethods: This article is a type of analytical research with a Case Control approach. The data analysis method used in this research is the Retrospective Approach method. To see the relationship between two variables, namely the independent variable and the dependent variable that occurred first. To test the hypothesis in this study, the Chi Square statistical test was used.Results: The results of the Chi-Square statistical test obtained P-Value = 0.000 (≤ 0.05) which means that there is a relationship between blood sugar levels and peripheral neuropathy disorders in patients with type 2 diabetes mellitus at the Tiban Baru Health Center Batam City in 2021. The results of the close relationship analysis were obtained OR = 22.22 (95% CI 1.906 - 88.428) people at the Tiban Baru Health Center who suffer from type 2 diabetes who experience uncontrolled blood sugar levels have a 22.22 times possibility of experiencing peripheral neuropathy compared to type 2 DM patients who experience blood sugar levels controlledConclusion:  From the correlation test, the value of OR = 22.22% means that uncontrolled blood sugar levels contribute 22.22% to peripheral neuropathy 77.78% is influenced by other factors